Communication Options of Linguistic Identity in Educational Discursive Space - Svitlana Piroshenko (Pedagogical Discourse, 2013)
The article considers the communication parameters of linguistic identity in the plane of verbal discourse. Reflecting meaningful and structured content of this term (linguistic identity), the author focuses on the individual, acting discursive space in specific communicative situations. She analyses multi-functional system of  performance and verbal approaches defined to the structure of linguistic identity. The author has drawn attention to the different classification of discourses of language education for speech work settings and types of verbal behavior of the individual. The type of discourse is a communicative phenomenon that, in the author’s opinion, reflects the characteristics of contemporary manifestations of linguistic identity.